DISRUPTIONS IN PROTEIN METABOLISM AND THE RESULTING DISEASES - Umurov Erkin Utkirovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Protein metabolism is a vital process for maintaining cellular structure and function, enzyme activity, and immune system integrity. Disruptions in protein metabolism can lead to various diseases, including protein-energy malnutrition, liver and kidney dysfunction, and muscle disorders. Imbalances in protein synthesis and degradation, along with deficits in essential amino acids, can cause significant metabolic consequences. This article explores the mechanisms behind protein metabolism, the pathophysiology of its disruption, and the diseases associated with these disturbances.